2019
DOI: 10.1002/cncr.32668
|View full text |Cite
|
Sign up to set email alerts
|

Nodal positivity decreases with age in women with early‐stage, hormone receptor–positive breast cancer

Abstract: Background Despite data demonstrating the safety of omitting axillary surgery in older women with early‐stage breast cancer, the incidence of axillary surgery remains high. It was hypothesized that the prevalence of nodal positivity would decrease with advancing age. Methods The National Cancer Data Base was used to construct a cohort of adult women with early‐stage, clinically node‐negative, estrogen receptor–positive (ER+), human epidermal growth factor receptor 2–negative breast cancer treated between 2013 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Preliminary studies have shown a decrease in rates of ALND and lumpectomy re-excision at both institutional and national levels. 2,11,12 In contrast, other studies suggest more than 80% of women 70 years and older with HR+ breast cancer receive SLNB 2,[13][14][15] and that CPM rates for patients with unilateral cancer are increasing. 2,16 While previous studies have examined some tumor-level, patient-level, and clinicianlevel determinants of persistent use, 17 to our knowledge, variation of deimplementation across facilities and procedures has not been described.…”
mentioning
confidence: 94%
“…Preliminary studies have shown a decrease in rates of ALND and lumpectomy re-excision at both institutional and national levels. 2,11,12 In contrast, other studies suggest more than 80% of women 70 years and older with HR+ breast cancer receive SLNB 2,[13][14][15] and that CPM rates for patients with unilateral cancer are increasing. 2,16 While previous studies have examined some tumor-level, patient-level, and clinicianlevel determinants of persistent use, 17 to our knowledge, variation of deimplementation across facilities and procedures has not been described.…”
mentioning
confidence: 94%
“…This is supported by other studies that have found the rate of nodal involvement among women 70 years of age or older with cN0, T1, ER+/HER2– IBC to be lower than 10%. 27 …”
Section: Discussionmentioning
confidence: 99%
“…AGING Lower BC-associated mortality in the elderly is notable considering challenges faced with providing aggressive standard of care therapies when limited by performance status and frailty measures, suggesting the development of relatively more indolent disease in the elderly with a less aggressive course. Congruently, multiple studies have characterized BCs in younger patients with higher histological grade, larger size, low or absent expression of ER and/or progesterone receptors (PR), and greater lymph node (LN) positivity [5][6][7][8][9][10]; while LN positivity in patients with early stage disease is found to be decreased with increasing age [11].…”
Section: Introductionmentioning
confidence: 99%